Tricks to reduce the incidence of obesity in children in Indonesia - Permaida Permaida (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
The annual incidence of childhood obesity in Indonesia is increasing. This increase was due to the low promotion of children's physical activity and nutritional education campaigns. This research aimed to collect evidence on how to design appropriate strategies to overcome the problem of obese children in Indonesia. The research used A literature review was conducted by searching the PubMed Central, BMC, BMJ, Science Direct, and PLOS One databases published between 2019 and June 2023 by analyzing data regarding program tricks to reduce obesity incidents in children using searches based on population (P), exposure (E), and results (O) as inclusion criteria. Only ten articles met the inclusion criteria. All articles discussed the importance of a healthy diet; 80% of articles discussed physical activity, which can quickly reduce obesity in children, and programs to overcome obesity in children face internal obstacles (60%) and external obstacles (80%). In conclusion, combining a healthy eating pattern program with physical activity is the main strategy for overcoming obesity in children. Strategies are also needed to minimize obstacles by establishing good cooperative relationships between parents and the community.